ENTREPRENEURIAL LEADERSHIP DAN STRATEGI SUKSESI GENERASI KETIGA PADA FAMILY BUSINESS DALAM MENGHADAPI PASAR BEBAS ASEAN (STUDI KASUS 3 PERUSAHAAN ROKOK DI MALANG) - Cynthia Dewi Subagio (Parsimonia - Jurnal Ekonomi dan Bisnis, 2018)
Family business in Indonesia, has an important role in contributing to state revenues. In order to support sustainability and to face competition, family business need to implement of entrepreneurial leadership and succession strategies. With the application of entrepreneurial leadership and appropriate succession strategy, the family business will get most benefits. The purpose of this study is to describe the succession strategy is the choice of the family business and analyze the implementation of entrepreneurial leadership family business of small local cigarette factory in the face of the ASEAN Free Trade. The experiment was conducted at three family business that have implemented entrepreneurial leadership and succession strategies with qualitative methods and techniques of data collection in the form of in-depth-interviews. The results showed that the succession strategy implemented three family business participants is a mix between Family Owned Enterprise (FOE) and the Family Business Enterprise (FBE) strategy. The participants also apply the type and dimensions of entrepreneurial leadership to face competition from local and foreign companies. The reason the participants to apply the type and dimensions of the entrepreneurial leadership of the company is the pressure from burdensome government family business of cigarettes field in Indonesia and the competition between local and foreign companies are increasingly stringent. The implications of this research for family business cigarette field to be ready to compete with local and foreign companies.